2013
DOI: 10.2147/rru.s39581
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stone composition in overweight and obese patients: a preliminary report

Abstract: ObjectiveTo report preliminary information on urinary stone composition in patients who are either overweight or obese with kidney stone disease.MethodsA cohort of patients (n = 138) with nephrolithiasis were prospectively followed from January 2011 for 18 months. Of those, 64 (46%) were found to be overweight with body mass index ≥ 25 kg/m2 and 74 (54%) were obese with body mass index ≥ 30 kg/m2. Stone characteristics including size, location, and composition were studied in detail, and patients’ age, weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
3
14
2
Order By: Relevance
“…UA stones are less common and comprise only 5 to 10% of all kidney stones [19][20]. Positive correlation between BMI and uric acid concentration in blood serum, which is involved in the pathogenesis of uronephrolithiasis, is compatible with other studies that have proved a connection between higher BMI and the formation of UA kidney stones [21][22][23][24]. Daudon and colleagues have reported that overweight and obese people develop calcium stones much less often than people with normal BMI, and the rate of UA stone formation increases with an increase in BMI [25].…”
Section: Components Of Metabolic Syndromesupporting
confidence: 71%
“…UA stones are less common and comprise only 5 to 10% of all kidney stones [19][20]. Positive correlation between BMI and uric acid concentration in blood serum, which is involved in the pathogenesis of uronephrolithiasis, is compatible with other studies that have proved a connection between higher BMI and the formation of UA kidney stones [21][22][23][24]. Daudon and colleagues have reported that overweight and obese people develop calcium stones much less often than people with normal BMI, and the rate of UA stone formation increases with an increase in BMI [25].…”
Section: Components Of Metabolic Syndromesupporting
confidence: 71%
“…11 Kidney stones mainly contain calcium oxalate, uric acid, struvite, cystine, and small amounts of phosphate and ammonium. 12 The main components of gallstones are cholesterol, bilirubin, bile acids, calcium apatite, and small amounts of magnesium and struvite. 13…”
mentioning
confidence: 99%
“…[3][4][5] These patients also had significantly higher total points when compared to calcium stone formers due to differences in demographic data and urinary parameters, in particular the lower urinary calcium. Prior studies have already demonnomogram to predict uric acid kidney stones strated some particularities in the 24-hour urine collections of uric acid stone formers and in patients with traits of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…2 Currently, several conditions have been linked to uric acid kidney stones, such as obesity, high blood pressure, diabetes, and low urinary pH. [3][4][5] Furthermore, 24-hour urine analyses have demonstrated that uric acid stone formers have a higher excretion of urinary sodium and a lower excretion of urinary calcium and oxalate when compared to calcium stone formers. 6 Imaging exams are also helpful when trying to distinguish between uric acid and calcium stones.…”
Section: Introductionmentioning
confidence: 99%